Differential effects of caffeine on hair shaft elongation, matrix and outer root sheath keratinocyte proliferation, and transforming growth factor‐β2/insulin‐like growth factor‐1‐mediated regulation of the hair cycle in male and female human hair follicles in vitro. (30th October 2014) - Fischer, T.W.; Herczeg‐Lisztes, E.; Funk, W.; Zillikens, D.; Bíró, T.; Paus, R.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Caffeine stimulates hair growth in androgen‐sensitive testosterone‐suppressed male human hair follicles (HFs) in vitro. What does this study add? The first evidence is presented for caffeine‐stimulated growth of female human HFs, which are more caffeine sensitive than male HFs. Proliferation is increased by caffeine in human HF matrix keratinocytes in situ and in HF‐derived outer root sheath keratinocytes (ORSKs). The catagen inducer transforming growth factor‐β2 is downregulated, and the anagen‐promoting factor insulin‐like growth factor‐1 is upregulated in human HFs in situ and in ORSKs.